2022
DOI: 10.3803/enm.2022.1573
|View full text |Cite
|
Sign up to set email alerts
|

Independent Skeletal Actions of Pituitary Hormones

Abstract: Over the past years, pituitary hormones and their receptors have been shown to have non-traditional actions that allow them to bypass the hypothalamus-pituitary-effector glands axis. Bone cells-osteoblasts and osteoclasts-express receptors for growth hormone, follicle stimulating hormone (FSH), thyroid stimulating hormone (TSH), adrenocorticotrophic hormone (ACTH), prolactin, oxytocin, and vasopressin. Independent skeletal actions of pituitary hormones on bone have been studied using genetically modified mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Several observational studies conducted in an adult population concluded that individuals with low normal TSH levels, regardless of TH levels, are at risk of developing osteoporosis [ 22 ]. However, BMD loss was more likely attributed to the diverse immune–skeletal–endocrine interactions between TSH in the bone marrow cells and TSH receptors in the skeletal tissues based on the osteoclastogenic effect of tumor necrosis factor α and the expression of splice variants of TSH [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies conducted in an adult population concluded that individuals with low normal TSH levels, regardless of TH levels, are at risk of developing osteoporosis [ 22 ]. However, BMD loss was more likely attributed to the diverse immune–skeletal–endocrine interactions between TSH in the bone marrow cells and TSH receptors in the skeletal tissues based on the osteoclastogenic effect of tumor necrosis factor α and the expression of splice variants of TSH [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to growing evidence, the JAK/STAT signaling pathway is important in bone development, metabolism, healing, and aging 38 , 39 . Growth hormone promotes bone growth and, when deficient, increases osteoclast activity, which can cause bone damage 40 . Figure 7 shows that compared to group C, growth hormone synthesis, secretion, and action were down-regulated in group B, whereas YWD could up-regulate the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that OT could reduce the proliferation and migration of three ovarian cancer cell lines, induce apoptosis and autophagy, and partially reverse the effects of cortisol ( Mankarious et al, 2016 ). With the in-depth study of the pituitary–bone axis, more sources of evidence prove that OT and OTR play an essential role in regulating bone metabolism ( Kim et al, 2022 ; Winterton et al, 2022 ). By reviewing the relationship progress between OT/OTR and bone marrow mesenchymal stem cells (BMSCs), osteoblasts (OB), osteoclasts (OC), osteocytes, adipocytes, and chondrocytes, the mechanism of OT/OTR in regulating bone metabolism is clarified, which can provide certain reference values to clinical application with their anti-osteoporosis effects.…”
Section: Introductionmentioning
confidence: 99%